Hubungan Antara Tingkat Pengetahuan Kesehatan Reproduksi Remaja dan Pencegahan Keputihan di SMK Muhammadiyah 1 Moyudan Sleman Yogyakarta - Tri Arini; Rista Islamarida; Maria Merdiana (Journal of Health (JoH), 2017)
Background: Reproductive health in women is not independent of the health of sex organs. Whitish is a symptom of disease characterized by discharge of fluid from the reproductive organs rather than blood. To be able to perform the attitude of prevention of whiteness required good knowledge to the student concerned. Purpose: Is know the relationship between the level of knowledge about the health of adolescent’s reproduction and the prevention of white discharge on student at SMK Muhammadiyah 1 Moyudan Sleman Yogyakarta Method: This is the non experiment research with quantitative method and Cross Sectional approach. This research is done at SMK Muhammadiyah 1 Moyudan Sleman Yogyakarta on March 2017. The data is collected by giving questionnaire Result: The result of this research is obtained that there are 43 students (84,3%) have a good level of knowledge about the health of adolescent’s reproduction and 8 students (15,7%) have enough level of knowledge. Where as, the determent demeanor of white discharge obtained 47 students (92,2%) have good demeanor and 4 students (7,8%) have bad demeanor. The result of statistic experiment is obtained correlation coefficient value (r) in the amount of r = 0,676 with significance p = 0,000 (p<0,05). Conclusion: There is the relationship between the level of knowledge about the health of adolescent’s reproduction and the prevention of white discharge on student at SMK Muhammadiyah 1 Moyudan Sleman Yogyakarta.